Lakshamana: New tamarind selection for improving rural livelihood - C, Kanupriya; G, Karunakaran; Singh, Pritee (Indian Horticulture, 2021)
Tamarind is a nutritious crop which has been growing in India since centuries. The tree is of widespread occurrence growing on marginal lands in semi-arid and sub-humid tropical climates, making it highly valuable in ensuring food security for rural poor. Given the great potential of this neglected and underutilized species to address global challenges such as hunger, poverty and climate change adaptation, there is a need to revisit research and development priorities in its favour and to develop strategies together with stakeholders to increase its use.